Application of Al2O3modified sulfate tailings (CaFe-Cake and SuFe) for efficient removal of cyanide ions from mine process water - Iakovleva, E.; Sillanpää, M.; Mangwandi, C.; Albadarin, A.; Maydannik, P.; Khan, S.; Srivastava, V.; Kamwilaisak, K.; Wang, Shaobin (Elsevier, 2018)
© 2018 Elsevier Ltd A novel approach for the management of solid and liquid wastes of mining was implemented in this work. Unmodified and modified metallurgical solid wastes, sulfate tailings, were used as adsorbents for the removal of cyanide ions from synthetic mine process water. Energy dispersive X-ray fluorescence (ED-XRF), scanning electron microscopy (SEM) and nitrogen adsorption methods, based on Brunauer-Emmett-Teller (BET) theory, were used for analysis of composition, structure and surface area of the adsorbents. A wet-granulation method was used for preparation of granules from sorbent powders with polyvinyl acetate as a binder and the further modification of the sorbent surface was carried out by atomic layer deposition (ALD) of Al 2 O 3 . The granules were used for the removal of cyanide ions from synthetic solutions by batch adsorption method. ALD-modified sorbent showed approximately 3.5 mmol g -1 adsorption capacity for cyanide ions. The adsorption isotherm was fitted with Langmuir and Freundlich adsorption models. The cyanide ions on the modified sorbent surface is enabled to form a stable and non-toxic cyanide complex in the solution, which can be reused as the complexing agent in the metallurgical industries.